2014
DOI: 10.1007/s10237-014-0614-4
|View full text |Cite
|
Sign up to set email alerts
|

Uterine peristalsis-induced stresses within the uterine wall may sprout adenomyosis

Abstract: Adenomyosis is a disease in which ectopic endometrial glands and stromal cells appear in the uterine myometrium. This pathology is common among women of reproductive age, and in addition to chronic pelvic pain and heavy periods it may also cause infertility. The 'tissue injury and repair' mechanism in response to increased intrauterine pressures was proposed as the etiology for migration of fragments of basal endometrium into the myometrial wall. In order to investigate this mechanism, a conceptual two-dimensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 28 publications
3
23
1
Order By: Relevance
“…Apart from its important role as an estrogen moderator, Sprr2a has wound healing and inflammation regulatory functions48 We found that Tff1 and Sprr2a1 were downregulated in the adenomyosis mouse model, implying that an increased estrogen level is associated with adenomyosis, and that an impaired wound healing ability of the endometrium may be involved in the development of adenomyosis. These findings are consistent with a recent study that identified a “tissue injury and repair” mechanism in the development of adenomyosis, in which uterine peristalsis led to the invasion of endometrial tissue into the myometrium, resulting in adenomyosis49 In the present study, Tff1 and Sprr2a1 were upregulated following GnRH agonist treatment, suggesting that GnRH agonists may decrease the production of estrogen and improve the repair capacity of the endometrium. Few studies have been carried out into the role of Aldh3b2 , and these are limited to neuroblastomas50 and keratinocytes,51 not adenomyosis.…”
Section: Discussionsupporting
confidence: 93%
“…Apart from its important role as an estrogen moderator, Sprr2a has wound healing and inflammation regulatory functions48 We found that Tff1 and Sprr2a1 were downregulated in the adenomyosis mouse model, implying that an increased estrogen level is associated with adenomyosis, and that an impaired wound healing ability of the endometrium may be involved in the development of adenomyosis. These findings are consistent with a recent study that identified a “tissue injury and repair” mechanism in the development of adenomyosis, in which uterine peristalsis led to the invasion of endometrial tissue into the myometrium, resulting in adenomyosis49 In the present study, Tff1 and Sprr2a1 were upregulated following GnRH agonist treatment, suggesting that GnRH agonists may decrease the production of estrogen and improve the repair capacity of the endometrium. Few studies have been carried out into the role of Aldh3b2 , and these are limited to neuroblastomas50 and keratinocytes,51 not adenomyosis.…”
Section: Discussionsupporting
confidence: 93%
“…[ 5 ] The frequency, amplitude, duration, and direction of muscle contractions were observed to change during the menstrual cycle in hormone-dependent ways. [ 6 ] Bulletti et al . [ 7 ] compared the UC patterns of women with or without endometriosis (EM) and found that patients with EM had UCs with higher frequency and greater basal muscle tone.…”
Section: Discussionmentioning
confidence: 99%
“…However, increased production of estrogen leads to chronic hyperperistalsis with further damage at the JZ and progression of the pathology. Recently, computational modeling of physical stresses with the uterine wall in response to uterine hyperperistalsis revealed relatively large stresses with high gradients in space and time in the vicinity of the JZ . This simulation provided support to the basic cause for the TIAR hypothesis.…”
Section: Uterine Disease Development and Infertilitymentioning
confidence: 62%